Implementation of the IPACK (Infiltration between the Popliteal Artery and Capsule of the Knee) block into a multimodal analgesic pathway for total knee replacement - Kandarian, Brandon (Korean J Anesthesiol, 2019)
BACKGROUND: The Infiltration between the Popliteal Artery and Capsule of the Knee (IPACK) block is a new anesthesiologist- administered analgesic technique for controlling posterior knee pain that has not yet been well studied in total knee arthroplasty (TKA) patients. We compared pain outcomes in TKA patients before and after implementation of the IPACK with the hypothesis that patients receiving IPACK blocks will report lower pain scores on postoperative day (POD) 0 than non-IPACK patients. METHODS: With Institutional Review Board approval, we retrospectively reviewed data for consecutive TKA patients by a single surgeon 4 months before (PRE) and after (POST) IPACK implementation. All TKA patients received adductor canal catheters and peri-operative multimodal analgesia. The primary outcome was pain on POD 0. Other outcomes were daily pain scores, opioid consumption, ambulation distance, length of stay, and adverse events within 30 days. RESULTS: Post-implementation, 48/50 (96%) of TKA patients received an IPACK block, and they were compared with 32 patients in the PRE group. On POD 0, the lowest pain score (median [10th–90th percentiles]) was significantly lower for the POST group compared to the PRE group (0 [0–4.3] vs. 2.5 [0–7]; P = 0.003). The highest patient-reported pain scores on any POD were similar between groups with no differences in other outcomes. CONCLUSIONS: Within a multimodal analgesic protocol, addition of IPACK blocks decreased the lowest pain scores on POD 0. Although other outcomes were unchanged, there may be a role for new opioid-sparing analgesic techniques, and changing clinical practice change can occur rapidly.